2012
DOI: 10.1111/inm.12006
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Nurse Incentive Program: Facilitating physical health care for people with mental illness?

Abstract: People with serious mental illness have increased rates of physical ill-health and reduced contact with primary care services. In Australia, the Mental Health Nurse Incentive Program (MHNIP) was developed to facilitate access to mental health services. However, as a primary care service, the contribution to physical health care is worthy of consideration. Thirty-eight nurses who were part of the MHNIP participated in a national survey of nurses working in mental health about physical health care. The survey in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 41 publications
0
19
0
10
Order By: Relevance
“…A recent evaluation of the MHNIP found that consumers received increased access to support, improved continuity of care and follow‐up, and reduced hospital admission rates (Department of Health and Ageing, ). Other studies have explored health professionals' perceptions of the MHNIP (Happell et al ., ; Hurley et al ., ) the demographic and clinical profile of consumers accessing the service (Meehan & Robertson, ), and the role of MHNIP in facilitating physical health care (Happell et al ., (), but there is a lack of research reporting on consumer perspectives of the MHNIP and the QOL outcomes. The purpose of this study was provide an opportunity for consumers to explore what is important to them in relation to their QOL and the mental health care they receive from the MHNIP.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A recent evaluation of the MHNIP found that consumers received increased access to support, improved continuity of care and follow‐up, and reduced hospital admission rates (Department of Health and Ageing, ). Other studies have explored health professionals' perceptions of the MHNIP (Happell et al ., ; Hurley et al ., ) the demographic and clinical profile of consumers accessing the service (Meehan & Robertson, ), and the role of MHNIP in facilitating physical health care (Happell et al ., (), but there is a lack of research reporting on consumer perspectives of the MHNIP and the QOL outcomes. The purpose of this study was provide an opportunity for consumers to explore what is important to them in relation to their QOL and the mental health care they receive from the MHNIP.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The personalisation agenda for people with SMI also featured in the National Service Framework for Mental Health in 1999 [9]. Similar approaches to care-coordination have been implemented internationally [10111213141516]. …”
Section: Introductionmentioning
confidence: 99%
“…A previous evaluation of MHNIP highlighted it was seen as significantly enhancing primary care services for those with mental health problems and allowing GPs to play a greater role in the management of mental health conditions (Meehan & Robertson, ). A further study has recommended that MHNIP provides integrated care for physical and mental health (Happell, Platania‐Phung, & Scott, ). International research also supports the finding that there can be challenges in sustaining an effective relationship between the GP and PCLN, with GPs noting a high turnover of staff. Retention of staff has been identified repeatedly as a major issue within the mental health workforce and linked to an increased risk to patient safety and of suicide (National Confidential Inquiry into Suicide and Homicide by People with Mental Illness, NCISH, ), along with increased organizational costs.…”
Section: Discussionmentioning
confidence: 99%